Do Donors Reduce Bilateral Aid to Countries With Restrictive NGO Laws? A Panel Study, 1993-2012. (February 2018) - Dupuy, Kendra; Prakash, Aseem
Foreign aid contributes to about 10% of gross domestic product (GDP) of developing countries. To distribute aid in recipient countries, Western donors increasingly rely on nongovernmental organizations (NGOs). Yet, since the mid-1990s, 39 developing countries have adopted laws restricting the inflow of foreign aid to NGOs operating in their jurisdictions. In response to these restrictions, have bilateral donors reduced aid, either as a punishment or because they cannot find appropriate NGOs for aid delivery? We explore this question by examining a panel of 134 aid-receiving countries for the years 1993-2012. We find that all else equal, the adoption of a restrictive NGO finance law is associated with a 32% decline in bilateral aid inflows in subsequent years. These findings hold even after controlling for levels of democracy and civil liberties, which suggests that aid reduction responds to the removal of NGOs from aid delivery chains, and not to democracy recession.